Exploring Public Sentiment on ChatGPT - An Analysis of Twitter Data - Wahyuni, Nurul Arifah; Amelia, Dhea Rizky; Al Khoiry, I’tishom (Universitas Negeri Semarang, 2024)
The rapid growth and widespread adoption of ChatGPT, an AI-driven natural language processing (NLP) tool developed by OpenAI, has garnered both positive and negative attention across various sectors. This study explores public opinion on ChatGPT using Twitter data. The methodology employs topic modeling techniques to identify the main topics discussed in relation to ChatGPT on the platform and conducts sentiment analysis to investigate public perceptions. This research is particularly relevant due to the recent release of the paid version of ChatGPT-4 by OpenAI. Understanding public sentiment and the main topics of conversation is essential to address potential risks, identify improvement opportunities, and ensure the ethical and responsible development of AI-driven NLP tools.